2021
DOI: 10.1007/s10143-021-01619-w
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in neurosurgery: a systematic review and meta-analysis

Abstract: Delirium is a frequent occurring complication in surgical patients. Nevertheless, a scientific work-up of the clinical relevance of delirium after intracranial surgery is lacking. We conducted a systematic review (CRD42020166656) to evaluate the current diagnostic work-up, incidence, risk factors and health outcomes of delirium in this population. Five databases (Embase, Medline, Web of Science, PsycINFO, Cochrane Central) were searched from inception through March 31st, 2021. Twenty-four studies (5589 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
0
24
2
Order By: Relevance
“…The incidence of POD is about 15%–20% in patients undergoing neurosurgery, 1 and a number of studies have shown that age is the independent risk factors of POD in neurosurgery patients. 19 Therefore, the incidence of POD might be higher in elderly neurosurgery patients.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of POD is about 15%–20% in patients undergoing neurosurgery, 1 and a number of studies have shown that age is the independent risk factors of POD in neurosurgery patients. 19 Therefore, the incidence of POD might be higher in elderly neurosurgery patients.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The incidence of postoperative delirium (POD) varies significantly among different surgical types. Recently, a systematic review conducted for 18 studies showed the incidence of POD was 19% in neurosurgery patients, 1 and over 40% occurred after deep brain stimulation implantation surgery. 2 POD significantly prolongs the length of hospital stay, 3 4 decreases survival rate 5 and is associated with long-term postoperative cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POD was found to occur in 7% of glioblastoma patients and was associated with longer hospital stays, a lower probability of discharge home, and decreased survival [ 129 ]. A meta-analysis of 5589 patients revealed that the incidence of POD after intracranial surgery was 19%, ranging from 12% to 26%, due to variations in clinical characteristics and delirium assessment methods [ 11 ].…”
Section: Postoperative Delirium In Neurosurgical Patientsmentioning
confidence: 99%
“…Among those patients undergoing intracranial surgery, 4.2% had serious POD, which is directly associated with impaired neurological function and extended rehabilitation [ 10 ]. A meta-analysis involving 5589 patients revealed that the incidence of POD after intracranial surgery ranges from 12% to 26% due to variations in clinical characteristics and delirium assessment methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%